Search for question

} \left.\frac{\mathrm{d} f}{\mathrm{~d} x}=\frac{x 2^{2}}{3^{x^{3}}}(\ln 4-x \ln 27)\right) \text { d) } \left.\frac{\mathrm{d} f}{\mathrm{~d} x}=\frac{x 2^{x^{2}}}{\left(3^{3^{3}}\right)^{2}}(\ln 4-x \ln 27)\right) \text { e) } \left.\frac{\mathrm{d} f}{\mathrm{~d} x}=x 2^{x^{2}} 3^{-x^{3}}(2 \ln 2-3 \ln 3)\right) \text { f) } \left.\frac{\mathrm{d} f}{\mathrm{~d} x}=\frac{x 2^{x^{2}}}{3^{x^{3}}}\left(\ln 4-x^{2} \ln 27\right)\right) \left.\frac{\mathrm{d} f}{\mathrm{~d} x}=\frac{2^{x^{2}}}{3^{3^{3}}}(2 \ln 2-3 x \ln 3)\right) \text { h) None of the answers shown here. }

Fig: 1

Fig: 2

Fig: 3

Fig: 4

Fig: 5

Fig: 6

Fig: 7

Fig: 8

Fig: 9

Fig: 10